PENGUATAN KOMUNITAS GEREJAWI DALAM PENGEMBANGAN IMAN DAN PELAYANAN MASYARAKAT PAROKI SANTO VINCENTIUS A PAULO MALANG - Jumilah, Bernadeta Sri; Wiwin, Wiwin; Herin, Bergita Layon; Haki, Stefania Erfi (Jurnal AbdiMas Nusa Mandiri, 2025)
Strengthening community is a fundamental aspect of community service, particularly in fostering a harmonious and empowered faith life. This was clearly reflected in the Catholic community of St. Vincentius a Paulo Parish, Malang, especially among the youth, whose focus was on nurturing faith and active engagement in both church and society. The program aimed to support young people in deepening their faith as part of their preparation for the sacrament of Confirmation. Community service activities were organized into four groups: SMP A, SMP B, high school students, and adults, with sessions conducted at Santa Maria Catholic Senior High School, Malang. The program used several methods: coordination, structured scheduling, team training, and catechetical formation. The results showed that community strengthening was carried out effectively based on the planned strategies and shared pastoral goals. Coordination between the parish priest, catechists, and local leaders produced a well-organized schedule. Collaborative training created synergy among the youth, enhancing their commitment to faith and active participation in church life. This structured approach successfully guided all participants toward receiving the sacrament with readiness and devotion. They actively participated in the sessions and showed improved understanding of the significance of community life as a foundation of faith. Moreover, this process motivated them to embody these values in their daily routines through active engagement in both church and social environments. The program ultimately strengthened their faith journey and equipped them with a deeper sense of responsibility and meaningful involvement within the Catholic community and wider society.